Majalah Sabili: Transisi Orde Baru ke Reformasi (1985-2000) - Irhas Fansuri Mursal; Gusmira Wita (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
The aimed of this study was to identify the development of Sabili from the New Orde era to Reformation era. This research included in the press history research that used historical research methods with some procedures, namely heuristics, source criticism, interpretation and historiography. The resulted of this study showed that Sabili was part of the Islamic movement pioneered by young Islamic activists in Indonesia. There were differences between Sabili during the new Orde and Reformation era. First, during the new Order era Sabili was present as an illegal magazine as a form of resistance to the New Orde, while during the reform era Sabili became a legal magazine. Second, during the new Orde era, the Sabili distribution system was carried out clandestinely and aimed at religious proselytizing activist groups, while during the Reformation period the distribution was open to the public. Third, during the New Orde era Sabili did not have an office, the name of the editor was disguised and used KTAI as a publisher, while during the reform era Sabili had a permanent office, the name of the editor used the real name and was managed by PT. Bina Media Sabili. Fourth, during the new Orde era, the Sabilis orientation was Islamic religious proselytizing, while during the reformation era Sabili preaching and business. Fifth, during the  new order era, Sabili's content focused on Islamic knowledge and news about the Islamic world, while during the reformation era, Sabili's content did not only contain Islamic knowledge and news of the Islamic world but also actual news about the national and Middle East socio-political conditions.